Applying Information Processing Theory in Islamic Educational Practices: A Systematic Review - Fitriani, Ayu; Suryana, Ermis; Zulhijra (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
Information processing theory, a major framework in cognitive psychology, explains how individuals perceive, process, store, and retrieve information during learning. This theory conceptualizes the human mind as a system that processes information through stages, including sensory memory, short-term memory, and long-term memory. In the context of education, understanding these cognitive processes offers valuable insights into how teaching strategies can be designed to align with students' mental processes. This paper provides a comprehensive review of the key components of information processing theory and examines its implications for teaching and learning. Using a literature review approach, the study finds that applying the principles of information processing in education can improve instructional effectiveness by enhancing students' attention, memory encoding, and retrieval. These processes foster active learning, leading to better retention and deeper understanding. Educators can create more effective learning environments by aligning their teaching methods with how students’ cognitive systems function. By promoting practices that engage students’ cognitive processes, this theory supports the development of critical thinking, problem-solving skills, and academic achievement. These findings have implications for instructional strategies that can be applied in Islamic education contexts, such as in madrasah or Islamic religious education classes, to enhance student engagement and the effective delivery of Islamic values. The paper highlights the importance of integrating cognitive psychology principles into educational strategies to optimize student learning outcomes.